Money and value: a synthesis of the state theory of money and original institutional economics - Georgios Papadopoulos (Editura ASE Bucuresti, 2013)
The paper proposes a synthesis of original institutional economics and in particular of the work of John R. Commons with the state theory of money, constructing a theoretical framework for the analysis of economic value in relation to money. The argument developed resists the naturalistic, individualistic, neoclassical analysis of value, proposing an account based on antagonism and negotiation framed by social institutions and more specifically by the institution of money. Money plays an active role in the process of the constitution of the system of prices, creating possibilities of mediation in the conflicts around the distribution of social production and contributing towards the establishment of ‘reasonable value’ in economic transactions.